Bioinspired self-healing, superliquiphobic and self-cleaning hydrogel-coated surfaces with high durability - Multanen, Victor (Philos Trans A Math Phys Eng Sci, 2019)
Bioinspired self-healing materials are being developed with intrinsic or extrinsic mechanisms. Some materials heal by an external stimulus, such as heat, UV light, pH, electric field and humidity. Hydrogels are among the commonly used materials, which can self-heal by application of an external stimulus. In this study, a self-healing polyacrylamide hydrogel was selected which is known to swell when exposed to water and heal. Silica nanoparticles were added to the hydrogel and a fluorosilane overcoat was used to produce a superliquiphobic surface with a low tilt angle and self-cleaning properties. A fused titania coating on the glass substrate was used to promote adhesion to hydrogel coatings. Hydrogel-based coatings exhibited the ability to repel water and oil, anti-icing properties down to −60°C, self-cleaning, the ability to maintain superliquiphobicity in hot environments up to about 95°C and high wear resistance. The hydrogel-based coating also demonstrated self-healing capability after hydration of a scratched surface. This article is part of the theme issue ‘Bioinspired materials and surfaces for green science and technology (part 2)’.